ANALISIS EFISIENSI DAN KELEMBAGAAN PEMASARAN JAGUNG DI KABUPATEN BENGKAYANG - Subejo, Jajat Sudrajat, Jangkung Handoyo Mulyo Slamet Hartono, (Jurnal Social Economic of Agriculture, 2014)
This research aim is to analyze the efficiency and institution of corn marketing. The study is done by using survey method. Primary data are collected comprises122 household’s farmers which are randomly selected. Meanwhile, there are nine traders selected by purposive sampling based on information of the farmer. The result of this research concluded some important informations, as follow: (a) the relationships among institutions of corn marketing is frequent based on the implementation of social value and norm (social capital) which is important role in improving efficiency and efectivity of whole institutional marketing, (b) based on whole (totality) of cost and benefit analyze which is obtained on each marketing institution, it can be concluded that the corn marketing has been done enough efficient. This reality can be shown by farmer’s share of corn price which is enough big that is 76.92 percent and the fact that every marketing institution has got logical benefit which is appropriate with its role. Keywords: efficiency, institution, social capital, farmer’s share